Kemampuan Berpikir Kreatif dan Komunikasi Matematika pada Mahasiswa Melalui Pembelajaran Open-Ended dengan Pendekatan Kontekstual - Mitra Permata Ayu; Supriadi Supriadi (Universitas Muhammadiyah Sorong, 2021)
The purpose of the study was to analyze the ability to think creatively and mathematical communication in writing and orally through open-ended learning with a contextual approach. This study uses a qualitative approach and this type of research is descriptive. The subjects in the study were 30 first semester students majoring in Informatics Engineering. Data collection methods used in this study were tests and interviews. The results showed that: 1) The overall creative thinking ability of students based on the originality aspect was 75.08%; fluence of 58.84%; the flexibility aspect is 52.98% and the elaboration aspect is 69.82%; 2) Overall written communication ability based on aspects of writing mathematical ideas by 70.87%; the aspect of representing the image is 71.57%; systematic aspects of completion of 73.68% and aspects of the use of notation by 67.36 and 3) Overall oral communication skills based on aspects, namely mentioning things relevant to the problem of 62.22%; the aspect of understanding the purpose of the question is 62.22% and the aspect of presenting is 60%.